2022
DOI: 10.1186/s40001-022-00839-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of platinum-based and non-platinum-based drugs on triple-negative breast cancer: meta-analysis

Abstract: Background Triple-negative breast cancer (TNBC), the subtype of breast cancer with the highest mortality rate, shows clinical characteristics of high heterogeneity, aggressiveness, easy recurrence, and poor prognosis, which is due to lack of expression of estrogen, progesterone receptor and human epidermal growth factor receptor 2. Currently, neoadjuvant chemotherapy (NAT) is still the major clinical treatment for triple-negative breast cancer. Chemotherapy drugs can be divided into platinum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Breast cancer treatments incorporating carboplatin, pembrolizumab, and anti-HER agents have notably increased pCR rates in triple-negative and HER2 subtypes (14,15). According to the data from the presented study, receptors for ER, PR, and HER2 may play pivotal roles in achieving pCR, with the literature corroborating lower pCR rates in luminal-A and luminal-B subtypes (8,9,16).…”
Section: Discussionsupporting
confidence: 67%
“…Breast cancer treatments incorporating carboplatin, pembrolizumab, and anti-HER agents have notably increased pCR rates in triple-negative and HER2 subtypes (14,15). According to the data from the presented study, receptors for ER, PR, and HER2 may play pivotal roles in achieving pCR, with the literature corroborating lower pCR rates in luminal-A and luminal-B subtypes (8,9,16).…”
Section: Discussionsupporting
confidence: 67%
“… 25 A study has shown that platinum-based chemotherapy can significantly improve the pathologic complete remission (PCR) rate and prognosis of patients with mTNBC, while chemotherapy regimens containing platinum compounds can significantly increase the incidence of adverse reactions such as thrombocytopenia and diarrhea. 55 Similarly, another study concluded that compared to non-platinum drugs, platinum drugs may cause more serious hematological adverse reactions in the treatment of TNBC. 56 Toxicity is clearly an important concern when using platinum-based drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of TNBC primarily involves chemotherapy and monoclonal antibodies, but recurrence rates remain high . Existing chemotherapy options for TNBCs include drugs like paclitaxel, docetaxel, doxorubicin, cabozantinib, Pt drugs, bevacizumab, and pembrolizumab. Platinum drugs, in particular, have shown improved clinical outcomes compared to non-Pt drugs but come with severe hematological toxicity and dose-dependent endothelial cell toxicity due to upregulation of ICAM-1 . Lymphatic endothelial cell autophagy increases their permeability and promotes metastasis.…”
Section: Introductionmentioning
confidence: 99%